Pengaruh Kepemimpinan Transforasional Kepala Sekolah, Iklim Kerja terhadap Kinerja melalui Motivasi Kerja - Dwi Fajarwati; Wahyu Wahyu; Novitawati Novitawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine and analyze the influence of the principal's transformational leadership and work climate through work motivation on teacher performance. This research is quantitative research with path analysis. The research population was 271 people with a research sample of 161 people. Data collection was carried out using an instrument consisting of the principal's Transformational leadership (27 items), work climate (26 items), work motivation (20 items), teacher performance (26 items) which had been tested for validity and reliability. Analysis of this research data uses path analysis (Path Analysis). The results of the study found that there was an influence of the principal's Transformational leadership on performance, work climate on performance, work motivation on performance, principal's Transformational leadership on work motivation, work climate on teacher motivation, principal's Transformational leadership on performance through work motivation, work climate on performance through work motivation. Keywords: Transformational leadership, work climate, work motivation, performance